Successful non-operative management of cauda equina syndrome in a case of thalassemia major - Rohit Khurana; Shilpa Khanna Arora; Alok Hemal; Sumit Arora (Pediatric Hematology Oncology Journal, 2016)
Thalassemia is associated with several challenging comorbidities. Here we report a 20 year old thalassemic who presented with cauda equina syndrome due to paraspinal extra medullary hematopoiesis (EMH) and was treated with hydroxyurea, repeated blood transfusions, and radiotherapy. Thus compressive myelopathy due to EMH was successfully managed conservatively.